Research on the Method of Improved Indexing Accuracy for Gear Shaper based on TE Detection and Control Theory - Yong Zheng; Donglin Peng; Yan Chen; Tianheng Zhang; Qiwu Zhou (Jixie chuandong)
In order to improve the indexing accuracy of CNC gear shaper YKD5132X3, the transmission error of gear shaper is detected. After analyzing the data, it is concluded that the main error sources of indexing error are workpiece worktable worm gear and cutter stand worktable worm gear pair. Aiming at these two error sources, the two worm gears are processed by the refined worm wheel master machine of our research group, and the on-line detection is realized through the on-line detection device. After the worm gear is finished, when the gear shaper is assembled, the installation of the workpiece worm gear is adjusted by TE data. The method of adjusting and installing many times in the past is replaced, which saves the installation time and improves the installation precision. Finally, the gear cutting accuracy of gear shaper is improved from 7-level to 5-level.